Plaque morphology in diabetic vs. non diabetic patients assessed by Multi-Slice Computed Tomography coronary angiography - Aboul-Enein, Hesham Mohamed; El Naggar, Amr Elsayed; Farag, Shereen Ibrahim; Hassan, Waleed Atef Ahmed (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background and Objectives: Multi-slice computed tomography (MSCT) provides high accuracy for noninvasive assessment of coronary artery disease (CAD). The introduction of the latest computed tomography technology allows comprehensive evaluation of various aspects of CAD, including the coronary calcium score, coronary artery stenosis, bypass patency, and myocardial function. This study aimed to assess the effect of DM on coronary arteries evaluated by MSCT-CA Comparing Plaque Morphology in Diabetic patients with Non-Diabetic Whoever Controlled or not assessed by HbA1c. Methods: In this study we randomly assigned 150 adult patients were diagnosed with suspected coronary artery disease underwent MSCT-CA for evaluation their coronaries regarding luminal stenosis, Plaque analysis, Remodeling index, SSS, SIS and Ca score. Results: There was statistically significant difference between diabetics & non-diabetic groups in LM lesions with (P = 0.029). also, the results of multivariate logistic regression analysis after adjustment for age and sex, diabetics were shown a trend toward more mixed plaque with statistically significant (OR): 3.422, 95% CI 1.66-7.023, P = 0.001; whereas, after adjustment for age, sex, history of hypertension, smoking, and hypercholesterolemia, patients with diabetes also shown a trend toward more mixed plaque with statistically significant (OR: 3.456, 95% CI 1.668-7.160, P = 0.001). It means significant differences in coronary atherosclerotic plaque burden and composition between diabetic and non-diabetic patients, with a higher proportion of mixed plaques, a more vulnerable form of atherosclerotic plaque in diabetics (P < 0.001) otherwise No significant difference. Conclusion: MSCT angiography may be useful for the identification of CAD in diabetic and non-diabetic patients. There were statistically significant differences in coronary atherosclerotic plaque burden and composition, with a higher proportion of mixed plaques, between diabetic and nondiabetic patients. Furthermore, MSCT may give accurate information about plaque characteristics according to different coronary risk factors, thereby identifying high risk features warranting a more intensive anti-atherosclerotic treatment.